Responses of complement C1q/tumor necrosis factor-related proteins to acute aerobic exercise. (January 2023) - Kon, Michihiro; Tanimura, Yuko
Highlights: Circulating CTRP1, CTRP3, CTRP5, and CTRP9 levels increase after aerobic exercise. A correlation between peak post-exercise levels of CTRP1 and TNF-α is seen. No correlation is observed between peak post-exercise levels of CTRP3 and insulin. Abstract: Aerobic exercise is an effective therapeutic strategy to manage metabolic disorders. However, the mechanisms of aerobic exercise-induced improvements in metabolic diseases are not completely understood. Complement C1q/tumor necrosis factor-related protein (CTRP) 1, CTRP3, CTRP5, and CTRP9 have important roles in improving metabolic disorders via the adenosine monophosphate-activated protein kinase signaling pathway. In this study, we investigated the effects of acute aerobic exercise on circulating CTRP1, CTRP3, CTRP5, and CTRP9 levels in human participants. Eight healthy males with an age of 20.4 ± 0.2 years, height 173.1 ± 1.7 cm, body mass 68.0 ± 1.8 kg, body mass index 22.7 ± 0.7 kg/m 2, and maximal oxygen uptake (VO2 max) 51.3 ± 2.5 mL/kg/min performed acute aerobic cycling exercise at 75 % of their VO2 max for 30 min (data are mean ± standard error). Blood samples were obtained before; immediately after; and 30, 60, and 120 min after exercising. Serum concentrations of CTRP1, CTRP3, CTRP5, CTRP9, tumor necrosis factor-α (TNF-α), and insulin were measured. The CTRP1 concentration significantly increased immediately after exercising and remained elevated for up to 120 min (p < 0.01). The CTRP3 concentration significantly increased at 60 min after exercise (p < 0.05), and the increasing trend continued until at least 120 min after exercise (p < 0.01). The CTRP5, CTRP9, TNF-α, and insulin concentrations significantly increased immediately after exercise (p < 0.05, p < 0.01, p < 0.05, and p < 0.05, respectively) and decreased thereafter. A significant correlation was observed between the peak post-exercise concentrations of CTRP1 and TNF-α (p < 0.05); however, no correlation was observed between the peak post-exercise concentrations of CTRP3 and insulin. The results of this study indicate that acute aerobic exercise may enhance the secretion of CTRP1, CTRP3, CTRP5, and CTRP9 in healthy adults.